Evaluation of Solar Energy Potential in Bojakan Village, Mentawai Islands Using PVGIS Simulation - Ikhsan, Alfikri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Electricity access remains highly uneven in Indonesia, especially in remote and underserved island regions such as the Mentawai Islands in West Sumatra. Bojakan Village, located in North Siberut District, is one of several communities still lacking electricity from the national utility grid (PLN). In response to this challenge, this study explores the technical feasibility of deploying solar photovoltaic (PV) systems as a renewable energy solution. Using hourly simulation data for a standard 1 kWp PV system from the Photovoltaic Geographical Information System (PVGIS), developed by the Joint Research Centre (JRC), energy production was analyzed over a three-year period (2021–2023). The data were processed in MATLAB to assess daily output, seasonal fluctuations, and average performance. Findings show that the PV system produces an average of 3.64 kWh/day. To meet the village’s projected electricity demand by 2031, a system with a capacity of approximately 49.7 kWp would be required, occupying a ground area of around 1,093.4 m². The results indicate that Bojakan holds sufficient solar potential for a sustainable off-grid energy system, subject to further technical and socio-economic considerations.